Pitting corrosion of triggering initial fractures of palm oil screw press machine shafts - Loganathan T.M.; Purbolaksono J.; Inayat-Hussain J.I.; Muthaiyah G.; Wahab N. (2023)
Investigation was carried out following the frequent occurrences of shaft failures in a number of palm oil screw press machines in a Malaysia palm oil mill company. Visual inspection, chemical analysis on the shaft material, fatigue analyses by utilizing traditional method and microscopic examinations were performed to support the investigation. Overview on pitting corrosion problems is presented. Common locations of the failure are at around bottom edges of keyway and shoulder fillets of the shafts. The findings indicate that pitting corrosion is identified as the main root causes of the premature shaft failures. In turn, poor surface condition would significantly reduce the fatigue endurance limit of the shafts under torsional loading. 2010 Elsevier Ltd.